2014
DOI: 10.1179/1743284713y.0000000382
|View full text |Cite
|
Sign up to set email alerts
|

Multiaxial cyclic viscoplasticity model for high temperature fatigue of P91 steel

Abstract: This paper presents a novel multiaxial, cyclic viscoplasticity material model for high temperature low cycle fatigue of P91 power plant steel. The model incorporates mechanisms-based variable strain-rate sensitivity and the key high temperature cyclic deformation phenomena of cyclic softening and non-linear kinematic hardening. The model has been calibrated to accurately represent the cyclic high temperature constitutive behaviour of ‘as received’ P91 steel. Details on the material Jacobian, with the consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…To enable more accurate extrapolation from the strain-rates conducted in laboratory experiments to the strain-rates typically observed in realistic plant [11,13,43], a hyperbolic sine material model is used to simulate strain-rate sensitivity and strain-rate independence of the material parameters. Thus, the flow rule for the increment in plastic strain is defined using the following equation set:…”
Section: Dislocation-based Materials Modelmentioning
confidence: 99%
“…To enable more accurate extrapolation from the strain-rates conducted in laboratory experiments to the strain-rates typically observed in realistic plant [11,13,43], a hyperbolic sine material model is used to simulate strain-rate sensitivity and strain-rate independence of the material parameters. Thus, the flow rule for the increment in plastic strain is defined using the following equation set:…”
Section: Dislocation-based Materials Modelmentioning
confidence: 99%
“…(4). Barrett et al (Barrett et al, 2014a;Barrett et al, 2013a;Barrett et al, 2013b) pointed out that a hyperbolic sine equation enables reliable extrapolation from strain-rates at which experiments are conducted to strain-rates typically observed in practical applications.…”
Section: Main Constitutive Equationsmentioning
confidence: 99%
“…In order for structural reliabilities to be ensured, a unified theory that could quantify the coupling effects between creep and viscoplasticity was important to be developed, furthermore identifying the underlying failure mechanisms [5,6]. Indeed, Professor Leen and his coworkers were successful in developing the unified constitutive models for utilized advanced steels in high temperature applications [7][8][9]. The results demonstrated that the proposed models could reproduce the material behavior accurately in cyclic plasticity, relaxation, and creep.…”
Section: Introductionmentioning
confidence: 99%